2016
DOI: 10.1371/journal.pone.0152183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Host Plant Factors on the Bacterial Communities Associated with Two Whitefly Sibling Species

Abstract: BackgroundAlthough discrepancy in the specific traits and ecological characteristics of Bemisia tabaci between species are partially attributed to the B. tabaci-associated bacteria, the factors that affect the diversity of B. tabaci-associated bacteria are not well-understood. We used the metagenomic approach to characterize the B. tabaci-associated bacterial community because the approach is an effective tool to identify the bacteria.Methodology and ResultsTo investigate the effects of the host plant and a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…In inflammation, neutrophils are the first arriving to inflammatory site and activate the host response. Neutrophils migrate from circulation to infected sites by crossing an endothelial layer, called neutrophil transmigration 36 and eliminate pathogens and protect the immunity 37 . The neutrophil recruitment is regulated by several adhesion molecules expressed on both neutrophils and endothelium 38 .…”
Section: Inflammation Disorders and Leukocytesmentioning
confidence: 99%
“…In inflammation, neutrophils are the first arriving to inflammatory site and activate the host response. Neutrophils migrate from circulation to infected sites by crossing an endothelial layer, called neutrophil transmigration 36 and eliminate pathogens and protect the immunity 37 . The neutrophil recruitment is regulated by several adhesion molecules expressed on both neutrophils and endothelium 38 .…”
Section: Inflammation Disorders and Leukocytesmentioning
confidence: 99%
“…In this study, the host plants tested strongly altered the composition of the microbial community (diversity and abundance) in spider mites. Similarly, research on Colorado potato beetles (Chung et al, 2017), whiteflies (Su et al, 2016), aphids (Guidolin & Cônsoli, 2016), and pine processionary moths (Strano et al, 2017) have shown that populations that fed on different plant species had differing microbial communities. Here, we found that spider mites that were switched from bean to other host plants experienced changes in bacterial community diversity and species richness, especially for the main bacterial species.…”
Section: Host Plant and Antibiotic Treatment Effects On The Spider mentioning
confidence: 99%
“…We hypothesized that our test population of Eastern MED (Q2), collected from a residence in Palm Beach County, would demonstrate a competitive disadvantage on tomato in relation to MEAM1 as MED had in China. However, given that the pest status of MED populations can be influenced by endosymbiont fauna, host plant, and history of exposure to insecticides, it is difficult to predict how MED populations in Florida will behave based on information derived from countries where growing conditions are in many ways distinct from Florida (Fang et al 2014;Mouton et al 2014;Fujiwara et al 2015;Su et al 2016). In addition, we present the results of probit analysis for imidacloprid and thiamethoxam tolerance from 2 MED populations collected from hibiscus (Hibiscus rosa-sinensis L.; Malvaceae) in Palm Beach County, and 13 MEAM1 populations collected from commercial vegetable fields in south Florida between late 2016 and mid-2017.…”
Section: Introductionmentioning
confidence: 99%